Juvenile Orders of Protection as a Remedy to Dating Violence, New York, 2009-2010 - Klein, Andrew R. ([Verlag nicht ermittelbar], 2023)
An increasing number of states, like New York, are expanding order of protection (OP) laws to allow juveniles and teens to secure orders for dating violence without parental involvement. New York amended its protective order law to cover victims of dating violence eighteen years and younger effective July 2008. While there has been extensive research in regard to civil OPs involving adults for intimate partner violence, this study of all OPs taken out by juvenile and teen victims of dating violence across New York State in 2009 and 2010 represents a first-of-its-kind examination of protective orders involving juveniles for dating violence. The goal of this research is to increase understanding of OPs taken out by juveniles and teens as a remedy for dating violence by developing a comprehensive portrait of their use in New York State, documenting the extent and patterns of re-abuse in cases when they are used, and exploring with the potential consumers, teens themselves, how they perceive these orders and the barriers they face in utilizing them. The specific aims of the study are: To provide a detailed description of the use of protective orders by juveniles and teens for dating violence, including who is securing them, against whom and for what, and whether petitioners (victims) return to court for permanent orders after securing temporary orders. To determine the courts' response to these orders, including the specific stipulations imposed. To determine the rate of order violations and other re-abuse reported to police in cases where orders have been obtained, as well as the victim, offender, incident, and order characteristics that ae associated with re-abuse up to two years after the order was first obtained. To explore in-depth with young people across the state their perspective about the use of civil protective orders among teens, including why these orders are underutilized and how to improve them to meet their unique needs.